Kreativitas Pesan dalam Iklan Layanan Masyarakat sebagai Upaya Mencegah Kasus Cyber Bullying - Laras Hati, Haninda Sekararum; Aurora, Catherine Naomi; Dite, Stri Agneyastra; Rachman, Anung; Rizkizha, Ditya Fajar; Naomi, Catherine (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2025)
Technological advancements in Indonesia bring benefits, but also trigger cyberbullying, which negatively impacts the mental, emotional, and social health of young people. This study aims to design an effective public service announcement (PSA) to raise public awareness and educate the public about the dangers of cyberbullying. Design thinking methods were used in this design process, through the stages of empathy, definition, ideation, prototyping, and testing. The result of this study is a public service announcement video that presents a narrative of the experiences of cyberbullying victims, a moral message, and solutions to overcome this problem. The video was uploaded to a digital platform to test its effectiveness through audience feedback. With a creative visual approach and relevant message, this PSA was able to raise public awareness and encourage behavioral changes to create a safer digital environment. The study recommends further development through cross-sector collaboration and ongoing education to maximize its impact.